Instructional Coaching Strategies in Collegiate Volleyball: An Adaptive Framework for Enhancing Technical Proficiency, Psychological Readiness, and Team Cohesion - Ahmad Ubaidillah; Dyas Andry Prasetyo; Andi Fepriyanto (Assyfa Learning Journal, 2026)
Effective coaching in collegiate sports requires an instructional framework that transcends traditional physical training to address the holistic needs of student-athletes. This study investigates the impact of diverse coaching methods—directive, collaborative, and observational—on the performance of undergraduate volleyball players within the Indonesian university context. Employing a sequential mixed-methods design, quantitative data were gathered from 56 undergraduate students at STKIP PGRI Sumenep via closed-ended questionnaires, complemented by structured interviews with six selected participants to gain in-depth qualitative insights. The findings reveal that while directive coaching is fundamental for foundational technical skill acquisition, collaborative methods are superior in fostering team cohesion and intrinsic motivation. Furthermore, observational coaching serves as an effective tool for reflective learning, though it requires integration with active instructional feedback to optimize immediate performance. The study concludes that an integrative, adaptive coaching framework—which dynamically balances directive clarity, collaborative participation, and reflective observation—is essential for enhancing holistic athlete development and team performance in higher education settings. These insights contribute to the Scholarship of Teaching and Learning (SoTL) by providing a replicable instructional model for coaches and sports educators aiming to harmonize technical excellence with psychological and social growth in competitive collegiate sports